Sintesis Precipitate Calsium Carbonat Sebagai Filler Pada Plastik Ramah Lingkungan - Sri Elfina; Novesar Jamarun; Akmal Djamaan (Politeknik ATI Padang, 2020)
Limestone is a mineral which is very abundant in Indonesia, especially in West Sumatra. Limestone is synthesized for making Precipitate Calcium Carbonate as a filler in plastics. The results of studies conducted on Precipitate Calcium Carbonate fillers from limestone based on X-RD, FTIR and SEMEDX analysis results, it can be concluded that the compound synthesized from limestone CaO is Precipitate Calcium Carbonate with aragonite and calcite crystal types. While the BET test showed a specific surface area of Precipitate Calcium Carbonate with a value of 7.315 m2 / g. Environmentally friendly plastic surfaces with the addition of Precipitate Calcium Carbonate filler were characterized using AFM obtained Rq value of 0.43 µm.